A lot like Christmas - Snow, Jennifer (Snow, Jennifer. Blue Moon Bay, 2021)
"Small-town bakery owner Jessica Connolly is officially done with dating. For the third time in a row, she's making a wedding cake for an ex who met the perfect woman after dating her... Dr. Mitch Jameson is emotionally exhausted from his last assignment with Doctors Without Borders. He's come home to Blue Moon Bay to recover with his family for the holidays before heading back to Cambodia. But a simple dessert pickup from the local bakery has him questioning everything..."--Page 4 of cover.